2011
DOI: 10.1146/annurev-food-022510-133640
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal Vaccination and Therapy with Genetically Modified Lactic Acid Bacteria

Abstract: Lactic acid bacteria (LAB) have proved to be effective mucosal delivery vehicles that overcome the problem of delivering functional proteins to the mucosal tissues. By the intranasal route, both live and killed LAB vaccine strains have been shown to elicit mucosal and systemic immune responses that afford protection against infectious challenges. To be effective via oral administration, frequent dosing over several weeks is required but new targeting and adjuvant strategies have clearly demonstrated the potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
82
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(83 citation statements)
references
References 125 publications
(115 reference statements)
0
82
0
1
Order By: Relevance
“…The mucosal surfaces represent the major portal of entry for pathogens, and it has been shown that it is possible to induce both systemic and mucosal immune responses via these surfaces (5). Promising results have been obtained with mucosal delivery of vaccine antigens through the intranasal, oral, or genital mucosal surfaces by both commensal and attenuated pathogenic bacteria (62). There has been much focus on vaccine delivery by attenuated pathogenic bacteria because of their intrinsic immunostimulatory properties, but such strains could potentially regain their virulence and, also, confer a risk to immunocompromised individuals (18).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The mucosal surfaces represent the major portal of entry for pathogens, and it has been shown that it is possible to induce both systemic and mucosal immune responses via these surfaces (5). Promising results have been obtained with mucosal delivery of vaccine antigens through the intranasal, oral, or genital mucosal surfaces by both commensal and attenuated pathogenic bacteria (62). There has been much focus on vaccine delivery by attenuated pathogenic bacteria because of their intrinsic immunostimulatory properties, but such strains could potentially regain their virulence and, also, confer a risk to immunocompromised individuals (18).…”
mentioning
confidence: 99%
“…Still, the use of nonpathogenic bacteria such as L. plantarum in immunization strategies usually does not result in complete protection against the disease, suggesting that vaccine adjuvants are needed to boost the immune response generated by the antigen-expressing bacteria (62). Early studies with LAB have shown that both systemic and mucosal immune responses improve substantially upon coexpression of adjuvants, such as interleukin-12 (IL-12) and IL-6, with an antigen (4,60).…”
mentioning
confidence: 99%
“…Many previous studies have demonstrated that commensal microbes carrying antigens can confer protective immunity (39,40). For example, recombinant Lactococcus lactis expressing the HIV type 1 (HIV-1) V2-V4 loop of Env induced antigen-specific immune responses that protected mice from challenge with recombinant vaccinia virus carrying the HIV env gene (41).…”
mentioning
confidence: 99%
“…51,52 Over the last decade recombinant probiotics have been generated for mucosal delivery of therapeutic and prophylactic molecules including DNA, peptides, single-chain variable fragments, cytokines, enzymes, and allergens. 53,54 The major advantages of probiotic bacteria as delivery system are their (1) ability to colonize mucosal surface, (2) tolerance to gastric acid and bile salts enabling survival and transit through the gastrointestinal tract (GIT), and (3) sustained colonization and prolonged protection against pathogen. 53,55 Furthermore, oral recombinant probiotics offer several advantages: direct delivery of active molecule to the mucosal surface without the need for bio-separation of the active molecules, increased shelf-life and stability, low delivery costs, and ease of technology transfer following prototype development.…”
mentioning
confidence: 99%
“…53,54 The major advantages of probiotic bacteria as delivery system are their (1) ability to colonize mucosal surface, (2) tolerance to gastric acid and bile salts enabling survival and transit through the gastrointestinal tract (GIT), and (3) sustained colonization and prolonged protection against pathogen. 53,55 Furthermore, oral recombinant probiotics offer several advantages: direct delivery of active molecule to the mucosal surface without the need for bio-separation of the active molecules, increased shelf-life and stability, low delivery costs, and ease of technology transfer following prototype development. This led to the concept of "biodrug" that is based on the oral administration of live recombinant microorganisms for the prevention and treatment of various diseases.…”
mentioning
confidence: 99%